Ovarian Teratocarcinoma in an Emu (Dromaius novaehollandiae): Histopathological and Immunohistochemical Characterization. (February 2018) - Leal de Araujo, J.; Perry, A.; Wild, J.; Kleinschmdit, L.; Hoppes, S.; Rech, R.R.
Summary: A 17-year-old female emu ( Dromaius novaehollandiae ) was presented for clinical evaluation due to a 3-week history of anorexia and progressive weight loss. The emu died after sedation. At necropsy examination, the ovary and the majority of the oviduct were effaced by a multinodular cystic mass and accompanied by 6 l of coelomic effusion. Histopathology revealed a neoplasm composed of well-differentiated, poorly organized tissues derived from ectoderm, mesoderm and endoderm. Tissues within the neoplasm expressed glial fibrillary acidic protein, desmin and cytokeratins AE1/AE3, respectively, confirming the diagnosis of teratocarcinoma. Graphical abstract: